PENGARUH FAKTOR-FAKTOR INTERNAL DAN EKSTERNAL TERHADAP PENGGUNAAN E-COMMERCE PADA USAHA KECIL MENENGAH (UKM) - , Raden Ajeng Intan K; , Sony Warsono, Dr.,MAFIS., Ak. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to examine and analyze the use of e-commerce on SMEs by developing a model of the Technology Acceptance Model (TAM) by adding a model of success sisem DeLone and McLean updated information, as well as combining with external variables of the dimensions of culture and environmental stress. The dimensions on this model is a system of quality, information quality, service quality, perceived usefulness, perceived ease of use, mimetic pressure, coercive pressure, normative pressure, uncertainty avoidance, in-group collectivism, intentions, and use. The research method used is a quantitative method that survey by using primary data by distributing questionnaires to SMEs in Indonesia. This study uses version 2.0 SmartPLS program as a tool to test hypotheses in the study. Based on the analysis above, all of the constructs in this study are qualified to test the validity and reliability testing. Based on the hypothesis testing results show that there are some supported the hypothesis H1a, H1c, H1d, H2a, H2b, H3b, and H4, and there is a hypothesis that is not supported is H1b, H3a, H3c, H3D, and H3E.